2000
DOI: 10.1007/s003350010071
|View full text |Cite
|
Sign up to set email alerts
|

CpG island libraries from human Chromosomes 18 and 22: landmarks for novel genes

Abstract: CpG islands are found at the 5' end of approximately 60% of human genes and so are important genomic landmarks. They are concentrated in early-replicating, highly acetylated gene-rich regions. With respect to CpG island content, human Chrs 18 and 22 are very different from each other: Chr 18 appears to be CpG island poor, whereas Chr 22 appears to be CpG island rich. We have constructed and validated CpG island libraries from flow-sorted Chrs 18 and 22 and used these to estimate the difference in number of CpG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…Nevertheless, we proceeded to utilize CGI arrays for three reasons. First, while chromosome 22 contains many CpG islands, chromosome 21 has relatively few (11,12). The proximity of p53BS to CGIs might be more accurately determined within a broader survey of CGIs in the human genome.…”
mentioning
confidence: 99%
“…Nevertheless, we proceeded to utilize CGI arrays for three reasons. First, while chromosome 22 contains many CpG islands, chromosome 21 has relatively few (11,12). The proximity of p53BS to CGIs might be more accurately determined within a broader survey of CGIs in the human genome.…”
mentioning
confidence: 99%
“…However, a GC-box as well as recognition sites for the rare cutter enzyme BssHII were found in the upstream region and in exon 1. The fact that the 5' region has a CG content over 60% indicates that CDCP1 contains a CpG island (Bird, 1986;Cross et al, 2000).…”
mentioning
confidence: 99%
“…An early study has indicated that content of CpG islands in human genome is chromosomedependent, with that Chr 18 is CpG island poor and Chr 22 CpG island rich (Cross et al, 2000). Recently, Antequera (Antequera, 2003) found that content of CpG islands in human genome is gene-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…CpG islands located in the gene PPRs play important roles in the reorganization of chromatin during mammalian spermiogenesis (Kundu and Rao, 1999) and in gene silencing during processes such as X-chromosome inactivation, imprinting, and silencing of intragenomic parasites (Takai and Jones, 2002). CpG islands are identified at the 5' end of approximately 60% of human genes and so are important genomic landmarks (Cross et al, 2000). Study of occurrence and characteristics of the CpG islands has gained great interests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation